Activity of Multinationals in Services - OECD eBooks (Paris : OECD Publishing.)
The measuring globalisation statistics provide comprehensive data on the industrial activity (manufacturing, service) of multinationals in OECD. It covers variables such as production, employment, research and trade, inward as well as outward investment. It also include some international trade indicators that provide cross-disciplinary background information.
Keywords: Industry and Services; Finance and Investment; Electronic books